Nitrogen behaviour during thermal drying of mechanically dewatered biosludge from pulp and paper industry. Issue 8 (18th April 2018) - Mustonen, Kati; Deviatkin, Ivan; Havukainen, Jouni; Horttanainen, Mika
ABSTRACT: An ongoing call to implement a circular economy is underway in the European Union, and a specific attention has been placed on the forest industry, which seeks additional recycling routes for its side streams, including biosludge. Biosludge is often dried and incinerated, thus wasting the nitrogen contained therein. This paper describes a study in which the release of nitrogen during thermal drying, the impact of the drying temperatures of 130°C, 180°C, and 210°C on the mass of ammonia released, and the potential for recovery of nitrogen from biosludge were examined. The results indicate that 1310–1730 mg kgTS −1 of nitrogen was released, which corresponded to 56–74% of the soluble nitrogen in biosolids or 4.0–5.3% of the total nitrogen. Of this released nitrogen, 83–85% was identified in condensate and absorbing water, thus indicating a high potential for recovering nitrogen from biosludge.